Study of Air Stability Index Threshold Values in the Event of Cumulonimbus Clouds and Thunderstorms at the Hasanuddin Meteorological Station - Hariansah, Agusmin; Jasruddin, Jasruddin; Susanto, Agus (Sahabat Publikasi, 2024)
The aim of this research is to analyze the characteristics and performance of the air stability index threshold values ??for Cumulonimbus (CB) and Thunderstorm (TS) cloud events. This research compares the results with previous data at the Hasanuddin Meteorological Station. The analysis was carried out using Showalter Index (SI), K Index (KI), Total-Totals (TT), and Convective Available Potential Energy (CAPE) data from 2013 to 2022 with the Sturges method to determine class intervals and frequency of occurrence. Then, the performance of the threshold value was tested with 2023 data using the 2x2 contingency table verification method. The analysis results show that the threshold values ??for the air stability index, especially SI, KI, TT, and CAPE, have changed compared to previous guidelines or research. These changes are mainly in the lower threshold values, with new values ??? (-5), ? (13), ? (32), and ? (1), respectively. This shows that the frequency of CB and TS events is still influenced by this threshold value, especially at the lower limit during cloud formation. However, performance analysis in 2023 does not yet show clear significance. In general, the sensitivity of the index in predicting short-term weather is better during the day than at night, showing consistency with previous studies.